THE INFLUENCE OF WORKLOAD, CONFLICT AND WORK ENVIRONMENT ON EMPLOYEES' JOB STRESS - Puspita, Ayu Ade; Subarjo, Subarjo; Gunawan, Hamzah (Proceeding Kilisuci International Conference on Economic & Business, 2023)
The aim of this research is to examine and analyze the influence of workload on employee work stress, conflict on employee work stress, and the influence of the environment on employee work stress at the Alexis Café, East Sumba Regency, NTT. The type of research is quantitative. The analytical tools used are validity and reliability tests using Smart (PLS) Version 3.0. PLS, with a Variance Based Structural Equation Modeling (SEM) approach. This research was conducted at Alexis Café, East Sumba Regency, NTT with a research population of 155 sources. The sampling method in this research used questionnaires and interviews so that the sample and population had the same size. The results show that workload has a positive and significant influence on work stress for employees of Alexis Café, East Sumba Regency-NTT, conflict has a positive and significant influence on work stress for employees of Alexis Café, East Sumba Regency-NTT, and the work environment has no effect on employee work stress. Alexis Café, East Sumba Regency-NTT.